Strengthening The Downstream of Robusta Coffee Products in Gunungjaya Village, Salem Sub-District, Brebes District - undri rastuti; purwati; purwanto; ary yunanto; siti badiatul umroh; sutarmin (Universitas Muhammadiyah Purwokerto, 2023)
Gunung Jaya Village, Salem District, there is a Joint Business Group (KUB)